Determinan Performance of People's Credit Bank (BPR) on the Provision of MSME Loans in Bogor District - Agus Kusmana; Ardhiani Fadila; Anggi Angga Resti (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2022)
This research is quantitative research whose aim is to determine the effect of v a r he b e l L D R, CAR, N P L and ROA te rh a d a p Lending Micro, Small and Medium Enterprises (SMEs) in Bogor . The population used in this study is Rural Banks (BPR) located in Bogor district, amounting to 22 BPRs. The method of determining the sample used is probability sampling, the number of selected BPRs is 18 BPR with a period of 2 years, so the number of samples is 36 data. The type of data used in this study is secondary data. Hypothesis testing in this study used panel data regression analysis using Microsoft Excel 2009 and E-Views version 10.0. The results of this study indicate that LDR, CAR, and BOPO have an influence on lending, whereas. NPL has no effect on lending